1996
DOI: 10.1063/1.361102
|View full text |Cite
|
Sign up to set email alerts
|

Fracture testing of silicon microcantilever beams

Abstract: Silicon microcantilever beams are fractured and characterized. The specially designed beams, etched into two wafers, are loaded to fracture in bending using a unique measurement system. A finite element model of the beams is created, and ABAQUS is used to calculate the displacements and stresses produced by an applied load force. A special testing scheme is devised to obtain certain model parameters: E͗110͘, the Young's modulus along the length of the beam and L force , the position of the applied force. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 10 publications
1
62
1
Order By: Relevance
“…Several of the important techniques include: the microtension test where the fracture strengths and Young's modulus can be estimated for non-integrated free standing structures [7][8][9]; the axisymmetric plate bend test is primarily used to measure the fracture strengths of relatively thick microstructures [10,11]; the microbeam bend test where a concentrated load is used to deflect the microstructure and is used for measuring Young's modulus, yield and fracture strengths of the microdevice [12,13]; the M-test where an electrostatic force is applied to bend thin microstructures in order to obtain experimental characteristics for Young's modulus and residual stresses [14,15]; the wafer curvature measurement method is used primarily for the quantification of residual stresses [16,17]; dynamic (resonance frequency) tests are suitable for measuring Young's modulus of elasticity and residual stresses in both thick and thin free standing microstructures [18][19][20][21]. These approaches require that the MEMS structure be excited in some fashion from its rest position and the changes measured either optically (interferometer, Doppler shift) or electrically (capacitive, resistive), for example.…”
Section: Mems Testing Methodsmentioning
confidence: 99%
“…Several of the important techniques include: the microtension test where the fracture strengths and Young's modulus can be estimated for non-integrated free standing structures [7][8][9]; the axisymmetric plate bend test is primarily used to measure the fracture strengths of relatively thick microstructures [10,11]; the microbeam bend test where a concentrated load is used to deflect the microstructure and is used for measuring Young's modulus, yield and fracture strengths of the microdevice [12,13]; the M-test where an electrostatic force is applied to bend thin microstructures in order to obtain experimental characteristics for Young's modulus and residual stresses [14,15]; the wafer curvature measurement method is used primarily for the quantification of residual stresses [16,17]; dynamic (resonance frequency) tests are suitable for measuring Young's modulus of elasticity and residual stresses in both thick and thin free standing microstructures [18][19][20][21]. These approaches require that the MEMS structure be excited in some fashion from its rest position and the changes measured either optically (interferometer, Doppler shift) or electrically (capacitive, resistive), for example.…”
Section: Mems Testing Methodsmentioning
confidence: 99%
“…The results showed that both testing methods and brittleness of the silicon lead to the variation of strength. Wilson et al [4] found that there is variation of bending strength of the SCS micro cantilever beam tested from front surface (3.3 GPa) and from back surface (1.0 GPa) due to anisotropic etching on the back surface. Detailed studies of the influence of chemical solution in wet etching on tensile strength of SCS were done by Taechung [5].…”
Section: Introductionmentioning
confidence: 98%
“…The nanoindenter has become a main measurement tool in recent years in the micro/nano-mechanics and materials field owing to its capability for high resolution force measurements [1][2][3][4]. There are several types of nanoindenters, for example, MTS Nano Indenter Ò (incorporated into Agilent in 2008), Hysitron TriboIndenter Ò , CSM Nano Hardness Tester Ò , MML NanoTest Ò and CSIRO UMIS Ò .…”
Section: Introductionmentioning
confidence: 99%